COMMUNITY HEALTH EDUCATION IN RILEY COUNTY - Rasmussen, Lindsey Nicole (My University, 2019)
Chronic diseases are on the rise in the American population and as such, the top killers have shifted from nonpreventable diseases to those that are preventable. Many of these diseases could be prevented through better diets and food choices (Slawson, Fitzgerald, & Morgan, 2013). Local health departments, health educators, and extension offices play a major role in this prevention through providing education, resources, and support for building healthier habits in families. These resources can be a leading force in making changes toward healthier families, which can help reduce the number of youths, and consequently adults, who develop obesity, Type 2 diabetes, and other chronic diseases (Ogagata & Hayes, 214). Chronic disease prevention, primarily through better nutrition and better diets, was the public health issue that was the main focus of my time at Lafene Health Center and the Riley County Extension Office. While at Lafene I worked with the Health Promotion office, whose purpose is to provide leadership in health maintenance promotion, and disease and illness prevention for Kansas State University students, staff, faculty and surrounding community members. The primary focus of my projects were to provide healthy eating tips, tricks, and education that is feasible with college students’ busy schedule, limited resources, and tight budget. This information was handed out at various health promotion events on campus. While at the Riley County Extension Office I planned and executed a healthy eating course for families, as well as a freezer meals class for community members. The healthy families course consisted of four one-hour classes that provided families with tools and resources to facilitate dialog, planning, and activities that would assist in developing healthier eating habits for the entire family. Due to unforeseeable circumstances, half of the courses had to be canceled but an increase in vegetable consumption was still reported among participants. At both locations, addressing the different socio-ecological barriers faced by the intended audiences increased the likelihood that participants would make healthier changes to their diets.
Keywords: Chronic disease; Nutrition; Community education